Histopathological evaluation of dental pulp of cat after using of sodium sulfonate in composite restorative treatment - Homayoun Alaghehmand; Maryam Seyedmajidi; Behzad Amiri- Andi; Neda Babaee (Babol University of Medical Sciences, 2013)
Introduction : Previous researches showed that neutral soaps significantly increased bond strength and decreased microleakage of dentin bonding agents. The aim of this study was histopathological evaluation of the effect of sodium sulfonate application as neutral soap on the cat's dental pulp after an ideal composite restorative treatment .  Methods: Ten adult cats with 40 caries-free canine teeth were selected for the study. Class V cavities were prepared in the buccal surfaces of all the teeth. The teeth of the right quadrants were treated with composite, whereas the teeth of the left quadrants were primarily etched, after using of sodium sulfonate solution, they treated with composite. The first five cats were killed after one week and the other five cats after one month. The teeth were fixed, decalcified and after being sliced, paraffined blocks were made and microscopic slides were prepared and histologically evaluated. Results: The results of the histological evaluation showed that there were no statistically significant differences between the intensity of inflammation in the pulp of the teeth in the right and left quadrants after one week (P=1.000) and one month (P=0.773). However, there was significant difference after one week regarding predentin formation (P=0.017) and in the teeth of the left quadrants, the formation of predentin was more that the right quadrants, but no meaningful difference was observed after one month (P=0.203).   Conclusion: It seems that the sodium sulfonate in composite restorative treatments without fear of damage to the pulp can be used.